SELECTION OF pEGFP-c1-TRANSFECTED-CHO-K1 CELLS BY G418 DECREASED THE EXPRESSION OF GREEN FLUORESCENT PROTEIN - Endah Puji Septisetyani; Adi Santoso (Indonesian Journal of Pharmacy, 2013)
The most common proteins used for reporter protein is the green fluorescent protein (GFP). It is very convenient to detect the GFP fluorescent by fluorescent microscopy or flowcytometry to monitor the successful transfection. The gfp gene can be introduced into the cells by transfecting of two different plasmid vectors or one vector containing both gfp and the gene of our interest. In this current experiment, we used pEGFP-c1 plasmid to express gfp in CHO-K1 cells. We transfected the CHO-K1 cells by using cationic lipid Lipofectamin 2000. We used this study as a way for predicting our human erythropoietin gene expression study in the CHO-K1 cells. In this study, we showed that expression of GFP decreased after incubation of the cells in selection medium containing G418. Expression of GFP seemed to be stable after about three weeks incubation in selection medium. Recombinant erythropoietin was also detected in the day 20. Key words: Ctionic lipid, CHO-K1 cells, erythropoietin, G418, green fluorescent protein